STATE OF PREPAREDNESS OF KENYA’S PUBLIC UNIVERSITIES TOWARDS DELIVERY OFCOMPETENCY BASED CURRICULUM - Paul Okeyo Ogembo (CV. ADIBA AISHA AMIRA, 2024)
Competency based curriculum (CBC) is a new dispensation in Kenya on its gradual replacement of 8:4:4 System of Education. The first cohort being in Grade Eight, Kenyan public universities seem not to be having measures in place towards its delivery. It is against this backdrop that this paper was purposed to assess the state of preparedness of Kenya’s Public Universities towards delivery of CBC.Specifically the paper sought to establish lecturers’ readiness for implementation of CBC;to establish universities’ infrastructural and curricula material preparedness toward implementation of CBC;to establish whether Kenya’s Public university schools of education are already preparing the teacher trainees towards teaching CBC programs and to establish Faculties’ attitudes towards CBC programs delivery. The study was underpinned by Concern Based Model by Hall et.al (2006). The study explored empirical literature through meta-analytical approach. The study established that: universities are not materially and infrastructural ready for implementation of CBC; That most lecturers are not ready for implementation of CBC; that many public universities are not yet training their teachers towards delivery of CBC programs; That university faculties have positive attitudes toward CBC programs. The findings have implications on universities and other stake holders to prepare lecturers for CBC, university management to look for means within their reach to help in funding and develop CBC curricula materials and infrastructure for its effective delivery, schools of education to develop teacher training curricula with CBC integration.